Sujeito e liberdade no pensamento de Michel Foucault - Santos, Maria Fernanda Cardoso (2012)
The leitmotif of this dissertation research is on the relationship between two fields of questioning in the Foucauldian works that may be considered, at a first glance, irreconcilable: the understanding of subject as the result of determinations, on the one hand, and its ethical stance of seeking the creation of liberty, on the other. Since, despite this apparent inconsistency, both ideas are present with much emphasis on the work of the French thinker, to understand the way Foucault articulated these two ideas was necessary to elucidate and interrelate the way in which he thought about the concepts of subject, power and liberty. Traveling with the author his intellectual itinerary, it was revealed that his conception of subject and liberty can be reconciled (although maintaining its problematic nature) and, also, both are inextricably linked each one as a result of the other. Tracing, with the author, his intellectual itinerary, it was also possible to identify and describe the fruitful conceptual tools for thinking about our own determinations and about the possibilities we have of creating new subjectivities and liberating experiences